Faktor Risiko Kejadian Hipertensi Pada Wanita Usia Subur di Wilayah Kerja Puskesmas Gunungpati Kota Semarang - Fuadi, Mirza Fathan; Sabela Naja, Zidna; Ary Yuniarti, Christina; Munandar, Aris (Jurnal Kesehatan, 2024)
Hypertension is a degenerative disease that many Indonesians suffer from. The prevalence of hypertension in Indonesia is around 30 percent with the incidence of cardiovascular disease complications being greater in women, around 52 percent, compared to men, namely 48 percent. Hypertension is a disease that is increasingly being found in the Gunungpati District of Semarang City, including many in Sadeng Village. From the preliminary study, it was found that 14 out of 20 respondents had hypertension with systolic blood pressure ranging between 120-177 mmHg with a mean of 155 mmHg and diastolic blood pressure ranging between 77-98 mmHg with a mean of 90 mmHg. The aim of this study was to determine the risk factors for hypertension in women of childbearing age in the Gunungpati Community Health Center working area, Semarang City. This research uses an analytical observational method with a cross-sectional design. The population of this study was 1,540 women of childbearing age with a sample of 101 women of childbearing age using purposive sampling technique. The variables studied were blood pressure, age, family history, exposure to cigarette smoke and stress. Data analysis using Chi-Square. The results of bivariate analysis showed that the significant variable was family history (p=0.013). Variables that were not significant were exposure to cigarette smoke (p=0.398) and stress (p=0.839). From this research, it can be concluded that respondents who have a family history of hypertension are at 2 times greater risk than women of childbearing age who do not have a family history of hypertension. To prevent hypertension, you can prevent it from an early age by adopting a healthy lifestyle such as doing enough physical activity and avoiding other risk factors.